THE TUBERCULOSIS TREATMENT OUTCOMES AND ASSOCIATED RISK FACTORS AMONG TUBERCULOSIS PATIENTS IN BULE HORA TEACHING HOSPITAL, SOUTHERN ETHIOPIA, 2021: RETROSPECTIVE CROSS SECTIONAL STUDY - Gelgelo, Dawit (Indonesian Journal of Community Health Nursing, 2025)
Background: In Ethiopia Tuberculosis is the leading causes of morbidity. The incidence of all forms of TB in the Ethiopia was 379/100000 population which is the second on the Africa continent. There are high discrepancies in the result of treatment outcome being reported from the different region of the country with frequent poor treatment outcomes particularly from the southern Ethiopia. Thus, this study aims to assess tuberculosis treatment outcomes and associated factors among tuberculosis patients in Bule Hora University Teaching Hospital, Southern Ethiopia Methodology: Facility based retrospective cross-sectional document review of 380 patients was conducted to assess the Tuberculosis treatment outcome and associated factors from tuberculosis patients' document registration. Data was entered into the computer using Epi-data software version 3.2 and exported to SPSS software version 25 for analysis. Bivariate and multivariate analysis with 95% confidence intervals were employed to infer associations between the independent and dependent variables. Result: The documents of 380 tuberculosis patients were reviewed. Among this patients, 87.9% were successfully treated where as 12.1% of the patients were unsuccessfully treated. From this, 53.4% and 34.5% patients were cured and completed the treatment, respectively, where as 3.7%, 5.8%, and 2.6% patients were died, treatment failure, and defaulted, respectively during the follow-up. Conclusion: The Tuberculosis treatment outcome for the present study was 87.9%, which was lower than national target which was >96% and global target >90% which required improvement. Among 12%.1 of unsuccessful TB treatment outcomes, 6.8% of them were HIV positive. The higher unsuccessful Tuberculosis treatment outcomes among HIV positive patients suggests the need to strengthen adherence education and supervision.